Transmission lines and wave propagation. - Magnusson, Philip C., ....-; Alexander, Gerald C., ....-; Triphati, Vijai K., ....- (Boca Raton : CRC, 2001)
Samenvatting:· Provides rigorous mathematical solutions for lossy and dispersivestructures, including fiber optic cable, and shows the uses of seriesapproximation· Presents graphs, transverse and orthographic views, and Lattice,Bergeron, and Phasor diagrams· Includes analysis methods for lossy and dispersive transmission linesand extends the results to Smith Chart calculations· Provides tables of pertinent mathematical functions, such as roots ofBessel, complementary error, and ground impedance functions· Emphasizes physical interpretation of results and graphically displaysmany illustrative cases.
Keywords: Radiogolfvoortplantingen; Telecommunicatieleidingen